Antisipasi Perang Siber: Postur Ketahanan Nasional Indonesia Merespon Ancaman Perang Siber - Rofii, Muhammad Syaroni (Jurnal Kajian Stratejik Ketahanan Nasional, 2018)
These days cyber war is considered to be one of the important issues that have become the focus of defense officials of major countries. Cyber war has the same damage effect as traditional war even more massive. A country's nuclear installations can be destroyed with the help of cyber soldiers. The energy source of a country can also be disabled with the help of cyber troops. Or creating chaos in a country's election such as US election in 2016 also involving cyber troops. The same situation also happened in Indonesia whereby official website of general election commission, public companies and private companies were targeted by cyber attacks. Because of the attacks those institutions lost their data. Considering increasing number of cyber attacks, it is very necessary to learn form the US experience. This article attempt to investigate the trends in cyber war and the dynamics surrounding it. The paper also propose some reccomendation related to the national security of Indonesia in responding cyber threats either from state or non-state actors.